Car plate detection system - Gunasegaran, Krishnan (2005)
Car Plate Recognition System is an image processing system in which it locates and recognizes a car plate. This technology is still new and only few systems are available in Malaysia. The most crucial part in Car Plate Recognition System is plate location. This is because if the system fails to detect the location of the car plate, then the whole system is a failure because recognition can only be done after successful plate location. Therefore, this research is mainly focused on plate location. In short, this research is entitled Car Plate Detection System. This system will focus on 4 major parts of pre-processing phase which are Image Enhancement using median filtering, Thresholding using global threshold value, Feature Extraction using thresholding, and Plate Location using rule-based conditions. This system was developed as a prototype to fulfill the requirement and prove the correctness of the algorithms used. The data or car plates used are strictly typical Malaysian civilian car plate numbers. Image is acquired using digital camera and fed to the system which thresholds the image to convert it into the binary image. Feature extraction is performed to produce the features of the binary image. Finally, the location of the car plate is located using rule based algorithms. The conditions are set as rule and the system detects the car plate if the condition exists. The results are discussed in Chapter 4.